Erratum – Some Remarks on the Protection of Legitimate Expectations in International Investment Law, in: “Comparative Law Review” (vol. 25) - Kałduński, Marcin (Comparative Law Review, 2021)
ERRATUM (At the request of the Author) The article entitled: “Some Remarks on the Protection of Legitimate Expectations in International Investment Law” by Marcin Kałduński, published in vol. 25 (2019) of the “Comparative Law Review” (pp. 215– –238) should include the following remark in the first footnote (p. 215): “The article has been published within the framework of the National Centre of Science’s project entitled «The Protection of Legitimate Expectations in International Investment Law» (Dec. No. DEC-2013/ 09/B/HS5/04127).”